Does the Technological Content of Government Demand Matter for Private R&D? Evidence from US States - Viktor Slavtchev; Simon Wiederhold (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2014)
Governments purchase everything from airplanes to zucchini. This paper investigates the role of the technological content of government procurement in innovation. We theoretically show that a shift in the composition of public purchases toward high-tech products translates into higher economy-wide returns to innovation, leading to an increase in the aggregate level of private research and development (R&D). Collecting unique panel data on federal procurement in US states, we find that reshuffling procurement toward high-tech industries has an economically and statistically significant positive effect on private R&D, even after extensively controlling for other R&D determinants. Instrumental-variable estimations support a causal interpretation of our findings. – – Der Staat beschafft eine Vielzahl unterschiedlicher Güter - von Autos bis Zucchini. In diesem Papier untersuchen wir die Rolle der technologischen Zusammensetzung der öffentlichen Beschaffung für Forschung und Entwicklung (FuE) in der Wirtschaft. Zunächst zeigen wir modelltheoretisch, dass eine relative Erhöhung der staatlichen Beschaffung in Hochtechnologie-Industrien die erwarteten Erträge aus erfolgreicher Innovationstätigkeit - und somit das Volumen an unternehmerischer FuE - erhöht. Mit Hilfe von administrativen Daten zu öffentlichen Beschaffungsaufträgen in U.S.-Bundesstaaten zeigen wir empirisch, dass eine Verschiebung der öffentlichen Beschaffung hin zu Hochtechnologie-Industrien tatsächlich einen positiven Effekt auf FuE in der Privatwirtschaft hat. Dieses Ergebnis bleibt auch bei Berücksichtigung einer Vielzahl von Kontrollvariablen erhalten. Instrumentenvariablen-Schätzungen unterstützen zudem eine kausale Interpretation der Ergebnisse.
urn:nbn:de:gbv:3:2-32152
Keywords: E60; H57; O31; O33; O38; 330; government demand; private R&D; endogenous growth; innovation policy; öffentliche Beschaffung; private FuE; endogenes Wachstum; Innovationspolitik; FuE-Politik